0439 A Polysomnographic Marker of Sleep Quality using Odds Ratio Product are Associated with Insomnia Symptoms in a Dose-Response Relationship. (25th May 2022) - Bender, Amy; Lambing, Kari; Gerardy, Bethany; Chalmers, Eric
Abstract: Introduction: Insomnia is primarily diagnosed with subjective complaints because objective biomarkers are limited. In the current study, we assessed whether a polysomnographic marker of sleep quality (odds ratio product; ORP) was associated with different types of insomnia symptoms. Methods: 416 participants (age 46.2±12.5; 176 females) recorded their sleep with an in-home Type 2 PSG test using the Cerebra Sleep System and filled out sleep questionnaires. Sleep quality was measured using odds ratio product (ORP) derived from frontal EEG channels across the duration of the recording (ORPTRT). On the questionnaires, participants reported whether they experienced any of the following insomnia symptoms at least three times a week: trouble falling asleep, trouble staying asleep, and waking up earlier than desired. Participants were then classified based on the total number of insomnia symptoms reported. An ANOVA, controlling for age, was performed to compare the effect of the number of insomnia symptoms on ORP. Results: 199 participants reported no insomnia symptoms, while the remaining 217 reported at least one symptom three nights a week (1 symptom: n = 62, 2 symptoms: n = 83, 3 symptoms: n = 70). There was a significant effect of number of insomnia symptoms on ORPTRT F(3, 414)=3.45, p =.017. There were significant differences between ORPTRT in participants who reported 0 symptoms (.991±.267), and participants who reported 2 symptoms (1.11±.259) (t(282) = -3.57, p <.001), and between 0 and 3 symptoms (1.13±.31 (t(269) = -3.46, p <.001). Even within individuals reporting insomnia symptoms, there were significant differences in ORPTRT between participants who reported 1 and 2 symptoms (p=.024), and 1 and 3 symptoms (p=.029). Conclusion: The more insomnia symptoms that were reported, the greater the impairment in sleep quality using ORP were found. Further research could explore if treatment interventions aimed at reducing ORPTRT might be useful to help treat insomnia. Support (If Any):